2007
DOI: 10.4049/jimmunol.178.8.5035
|View full text |Cite
|
Sign up to set email alerts
|

Autoantigen-B Cell Antigen Receptor Interactions That Regulate Expression of B Cell Antigen Receptor Loci

Abstract: Levels of AgR (BCR) expression are regulated during B cell development, activation, and induction of tolerance. The mechanisms responsible for and consequences of this regulation are poorly understood. We have described a class of DNA-based autoantigen-reactive B cell that down-regulates BCR expression during development to mature follicular phenotype. In this study, we show that at immature stages of primary differentiation, individual B cells of this type can dynamically modulate levels of expression of BCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 69 publications
2
28
0
Order By: Relevance
“…inhibited in bone marrow cultures by the monovalent form of Ars, Ars-Tyr (25). Our finding that Ars-Tyr treatment also decreased the level of binding of a FITC-labeled form of DNase I to the surface of canonical HKIR B cells supported the idea that downregulation was due to reduction of binding of canonical HKIR BCRs to a DNA-based autoantigen present in the cultures.…”
Section: Down-regulation Of the Bcr On Canonical Hkir B Cells Developsupporting
confidence: 76%
See 3 more Smart Citations
“…inhibited in bone marrow cultures by the monovalent form of Ars, Ars-Tyr (25). Our finding that Ars-Tyr treatment also decreased the level of binding of a FITC-labeled form of DNase I to the surface of canonical HKIR B cells supported the idea that downregulation was due to reduction of binding of canonical HKIR BCRs to a DNA-based autoantigen present in the cultures.…”
Section: Down-regulation Of the Bcr On Canonical Hkir B Cells Developsupporting
confidence: 76%
“…We previously reported that the rate of BCR internalization in immature HKIR/V10 B cells was higher than in control B cells in bone marrow cultures, but that these differences disappeared when Ars-Tyr was added to the HKIR/V10 cultures (25). Combined with the data presented, these findings suggested that the canonical HKIR BCR might mediate efficient uptake of a DNA-based autoantigen, allowing delivery to endosomes and activation of TLR9.…”
Section: Primary Development Of Canonical Hkir B Cells Is Not Alteredsupporting
confidence: 60%
See 2 more Smart Citations
“…1). In addition, neither HKIR/Vk10 nor HKI65/Vk10 clonotypes displayed any evidence of an anergic phenotype in in vitro studies analogous to those previously conducted on canonical clonotypes in HKIR and HKI65 mice (53).…”
Section: All B Cells Express Canonical E4mentioning
confidence: 64%